2000
DOI: 10.1046/j.1464-410x.2000.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Doxazosin: a new cytotoxic agent for prostate cancer?

Abstract: Objective To determine the sensitivity of drug-resistant prostate cancer cell lines to doxazosin-mediated cell death, and the effects of combining doxazosin and chemotherapeutic agents on these cell lines. Materials and methods The cytotoxic effect of doxazosin was initially evaluated in the prostate carcinoma cell lines DU145 and PC-3. Doxazosin was combined either with adriamycin, etoposide or paclitaxel after its cytotoxic effects were detected in these cell lines. The tetrazolium dye (MTT) assay and trypan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The established safety and efficacy of dox, along with its potent antiproliferative and proapoptotic effects, make it an attractive potential therapy for pituitary adenomas, particularly because we observed inhibition of pituitary tumor cell proliferation with similar or lower dox concentrations than those previously shown to inhibit prostate cancer growth. Furthermore, dox treatment with approved doses reduced growth and induced apoptosis in patients with prostatic hyperplasia (14,15,33). The results presented here indicate the potential utility of dox treatment in pituitary tumors not only to inhibit tumor growth and induce tumor regression but also to inhibit cytokine-mediated corticotroph tumor hormone secretion.…”
Section: Fig 7 Dox Treatment Inhibits Pituitary Corticotroph Tumor mentioning
confidence: 62%
See 1 more Smart Citation
“…The established safety and efficacy of dox, along with its potent antiproliferative and proapoptotic effects, make it an attractive potential therapy for pituitary adenomas, particularly because we observed inhibition of pituitary tumor cell proliferation with similar or lower dox concentrations than those previously shown to inhibit prostate cancer growth. Furthermore, dox treatment with approved doses reduced growth and induced apoptosis in patients with prostatic hyperplasia (14,15,33). The results presented here indicate the potential utility of dox treatment in pituitary tumors not only to inhibit tumor growth and induce tumor regression but also to inhibit cytokine-mediated corticotroph tumor hormone secretion.…”
Section: Fig 7 Dox Treatment Inhibits Pituitary Corticotroph Tumor mentioning
confidence: 62%
“…␣ 1 -Adrenergic receptors are further subdivided into ␣ 1A , ␣ 1B , and ␣ 1D subtypes (13), and antagonists include quinazolinebased prazosin, doxazosin (dox), and terazosin and the sulfonamide derivative tamsulosin. They are used to treat systemic hypertension (14) but have also been reported to inhibit growth and induce apoptosis in prostate cancer and reduce prostate-specific antigen levels (15,16).…”
mentioning
confidence: 99%
“…In vitro studies provide substantial evidence that the quinazoline α-antagonists doxazosin, terazosin and prazosin exhibit cytotoxic activity in the prostate cancer cell lines LNCaP (androgen-dependent), DU145 and PC-3 (castrate-resistant) cell lines [38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,84,85,86,87]. The structurally similar piperazine, naftopidil, also produced cytotoxic effects in the androgen-dependent LNCaP and E9 cell lines [88].…”
Section: Discussionmentioning
confidence: 99%
“…33 Confirming support for our data came from another independent study that was recently reported. 35 Although originally designed as antagonists of a 1 -adrenoceptors, recent mechanistic studies have implicated a non-a 1 -adrenoreceptor mediated mechanism of apoptotic action of doxazosin and terazosin in prostate cancer cells. 33 The studies summarized in Table 1 provide a strong argument in support of a growth regulatory effect of a 1 -adrenoceptor antagonists in the prostate and raise the possibility that programmed cell death of prostate cancer cells occurs via an effect mediated by the quinazoline component of the drugs.…”
Section: Discussionmentioning
confidence: 99%